Nicotine Effects and Receptor Expression on Human Spermatozoa: Possible Neuroendocrine Mechanism - Condorelli, Rosita A.; La Vignera, Sandro; Giacone, Filippo; Iacoviello, Linda; Mongioì, Laura M.; Li Volti, Giovanni; Barbagallo, Ignazio; Avola, Roberto; Calogero, Aldo E. (Frontiers in Physiology, 2017)
The aim of this experimental study was to investigate the mechanism by which nicotine (NIC) alters spermatozoa and to evaluate the expression of nicotinic receptors (nAChR) subunits in human spermatozoa. We analysed 30 healthy normozoospermic men. Spermatozoa were incubated with NIC 100 ng/ml and the nAChR antagonist, hexamethonium (HEX) (0, 100, 1000, 10000 ng/ml) for 3 and 24 hours. The following sperm parameters evaluated: a) progressive motility; b) mitochondrial membrane potential (MMP); c) chromatin compactness; d) externalization of phosphatidylserine (PS); e) late apoptosis; f) viability; g) DNA fragmentation; h) degree of lipid peroxidation (LP) by flow cytometry; i) nAChR subunits expression by quantitative Real Time PCR and j) protein expression evaluation by Western blot analysis. HEX fully antagonized the effects of NIC both after 3 and 24 hours of incubation with significant improvement (p<0.05) of sperm progressive motility, MMP, abnormal chromatin compactness, PS externalization, late apoptosis and DNA fragmentation, already at the concentration of HEX 100 ng/ml. The degree of LP increased after incubation with NIC in raw semen but this effect was fully antagonized (p<0.05) by HEX after 3 and 24 hours of incubation. Finally, 8 nAChR subunits mRNA (α1, α3, α4, α6, α7, β2, β4, and δ) were found expressed in all samples examined, but only α7 subunit is translated, making an homomer receptor, in non-smokers subjects. The effects of NIC on sperm function are mediated by interaction with a specific nicotinic receptor. The presence of nAChR subunits suggests the presence of a neuroendocrine mechanism on human spermatozoa.